TECHNICAL GUIDANCE ON PREPARING CORPORATE SOCIAL RESPONSIBILITY REPORTING FOR COMPANIES IN KENDARI - Anto, La Ode; Hadisantoso, Erwin; Awaluddin, Ishak; Fasihu, La Ode Muhammad Saum; Zaikin, Muhammad; Alfiansyah, Muhammad Andri; Ode, Tasya Aulia wa (International Journal of Engagement and Empowerment (IJE2), 2025)
This community service activity aims to increase the company's understanding and ability to compile and disclose Corporate Social Responsibility (CSR) in accordance with the Global Reporting Initiative (GRI) sustainability reporting standards. This program is carried out through Technical Guidance (Bimtek) activities to three companies in Kendari City, namely PT Bank Muamalat Kendari Branch, PT Jamkrindo Kendari Branch, and PT Satu Tiga lima Sejahtera Kendari. The implementation method includes three main stages, namely program technical guidance, the implementation of mentoring programs, as well as guidance, monitoring, and evaluation activities. The results of the activity showed a significant increase in the understanding, knowledge, and skills of the company's finance department employees in preparing financial statements that contain CSR disclosures in accordance with GRI and Sustainability Reporting Standards (SPK). Participants showed high enthusiasm and gave positive responses to the material, report preparation practices, and live demonstrations. In addition, this activity succeeded in producing outputs in the form of CSR disclosure formats in financial statements that can be used as a reference for partner companies. These findings are in line with the theory of corporate social responsibility which states that CSR is a company's commitment to contribute to sustainable development through a balance between economic, social, and environmental aspects (Carroll, 1999; Elkington, 1997). This activity is expected to strengthen the awareness of companies in Kendari City on the importance of transparency and accountability in CSR reporting and be the first step towards sustainable corporate governance.